2020
DOI: 10.3389/fvets.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Gap Arthroplasty in Cats

Abstract: Temporomandibular joint (TMJ) ankylosis is defined as fibrous or bony fusion of the mandibular head of the condylar process and the mandibular fossa of the squamous part of the temporal bone. Ankylosis of the TMJ may be intraarticular, extraarticular, or both. The objective of this report is to describe the surgical planning, technique, and outcome of gap arthroplasty for extensive TMJ ankylosis in cats. Client-owned cats (n = 7) were examined clinically and surgical planning included the use of cone-beam comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…[28][29][30] Recently, piezoelectric bone surgery technology has been recommended in maxillofacial surgery in veterinary patients due to its ability to selectively cut mineralized tissue in delicate places, significantly reducing the trauma to underlying soft tissue (eg, neurovascular bundle, muscles, etc). 21,31 As previously reported in patients that underwent gap arthroplasty or condylectomy, 9,12,21 all specimens in the present study showed mandibular drifting after performing segmental mandibulectomy. This postoperative complication is considered acceptable in clinical cases; as the patient can eat, drink and groom itself, selective dental extractions may be required to avoid further oral soft tissue trauma.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[28][29][30] Recently, piezoelectric bone surgery technology has been recommended in maxillofacial surgery in veterinary patients due to its ability to selectively cut mineralized tissue in delicate places, significantly reducing the trauma to underlying soft tissue (eg, neurovascular bundle, muscles, etc). 21,31 As previously reported in patients that underwent gap arthroplasty or condylectomy, 9,12,21 all specimens in the present study showed mandibular drifting after performing segmental mandibulectomy. This postoperative complication is considered acceptable in clinical cases; as the patient can eat, drink and groom itself, selective dental extractions may be required to avoid further oral soft tissue trauma.…”
Section: Discussionsupporting
confidence: 79%
“…2,6,11,12,[19][20][21] The postoperative recurrence is associated with the inability to remove extensive areas of affected tissue owing to its proximity to vital structures such as the base of the skull and the maxillary neurovascular bundle. 2,11,[19][20][21] While the segmental mandibulectomy between the fourth premolar and first molar teeth had previously been proposed as a possible treatment for unilateral TMJA, 22,23 veterinary practitioners have raised questions regarding which area of the mandible should be addressed and how much bony tissue must be removed. To the best of our knowledge, the specific area of the mandible and amount of bony tissue that must be excised during a segmental mandibulectomy in cats affected by unilateral TMJA has not been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lateral approach to the TMJ was performed as described in an earlier study (20,21). A full-thickness skin incision along the FIGURE 1 | Illustration of the topographic bone and cartilage anatomy of the left temporomandibular joint (TMJ) and its proximity to the tympanic bulla.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A lateral approach to the TMJ was performed as described in an earlier study ( 20 , 21 ). A full-thickness skin incision along the caudoventral aspect of the zygomatic arch was performed.…”
Section: Introductionmentioning
confidence: 99%